Human influence and biotic homogenization drive the distribution of Escherichia coli virulence genes in natural habitats. Issue 3 (18th February 2017) - Cabal, Adriana; Vicente, Joaquin; Alvarez, Julio; Barasona, Jose Angel; Boadella, Mariana; Dominguez, Lucas; Gortazar, Christian
Abstract: Cattle are the main reservoirs for Shiga‐toxin‐producing Escherichia coli (STEC), the only known zoonotic intestinal E. coli pathotype. However, there are other intestinal pathotypes that can cause disease in humans, whose presence has been seldom investigated. Thus, our aim was to identify the effects of anthropic pressure and of wild and domestic ungulate abundance on the distribution and diversity of the main human E. coli pathotypes and nine of their representative virulence genes (VGs). We used a quantitative real‐time PCR (qPCR) for the direct detection and quantification of the genus‐specific gene uid A, nine E. coli VGs ( stx1, sxt 2, eae, ehx A, agg R, est, elt, bfp A, inv A), as well as four genes related to O157:H7 ( rfb O157, fli CH7 ) and O104:H4 ( wzx O104, fli CH4 ) serotypes in animals (feces from deer, cattle, and wild boar) and water samples collected in three areas of Doñana National Park (DNP), Spain. Eight of the nine VGs were detected, being inv A, eae, and stx 2 followed by stx 1, agg R, and ehx A the most abundant ones. In quantitative terms (gene copies per mg of sample), stx 1 and stx 2 gave the highest values. Significant differences were seen regarding VGs in the three animal species in the three sampled areas. The serotype‐related genes were found in all but one sample types. In general, VGs were more diverse and abundant in the northern part of the Park, where the surface waters are more contaminated by human waste and farms. In the current study, we demonstrated that human influence is more relevant than host species in shaping the E. coli VGs spatial pattern and diversity in DNP. In addition, wildlife could be potential reservoirs for other pathotypes different from STEC, however further isolation steps would be needed to completely characterize those E. coli . Abstract : Cattle are the main reservoirs for Shiga‐toxin‐producing Escherichia coli (STEC), the only known zoonotic E. coli pathotype. However, there are other intestinal pathotypes that can cause disease in humans, whose presence has been seldom investigated, and in particular in wildlife. Thus, our aim was to identify nine E. coli virulence genes (VGs) and four genes related with O157:H7 ( rfb O157, fli CH7 ) and O104:H4 ( wzx O104, fli CH4 ) serotypes in animals (feces from deer, cattle and wild boar) and water samples collected in three areas of Doñana National Park (DNP), Spain.